1999
DOI: 10.1161/01.cir.99.15.1991
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Left Ventricular Mass and Endothelium-Dependent Vasodilation in Never-Treated Hypertensive Patients

Abstract: Our data provide the first evidence that echocardiographic LVM in hypertensive patients is inversely related to FBF responses to the endothelium-dependent vasodilating agent ACh, but it is likely that both endothelium and LVM are damaged by hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 45 publications
4
46
0
5
Order By: Relevance
“…39,40 However, in the multivariate analysis adjusting for a number of relevant confounding factors, LV mass index emerged as a significant independent correlate of the FMD, with a moderately strong adjusted standardized correlation coefficient. This was expected based on finding reported by Perticone et al, 41 who described lower forearm blood flow increase by acetycholine in patients with LVH vs those with normal LV mass. In addition, however, we showed that LV chamber and midwall systolic function were not significant correlates of FMD, which was not previously reported.…”
Section: Discussionsupporting
confidence: 75%
“…39,40 However, in the multivariate analysis adjusting for a number of relevant confounding factors, LV mass index emerged as a significant independent correlate of the FMD, with a moderately strong adjusted standardized correlation coefficient. This was expected based on finding reported by Perticone et al, 41 who described lower forearm blood flow increase by acetycholine in patients with LVH vs those with normal LV mass. In addition, however, we showed that LV chamber and midwall systolic function were not significant correlates of FMD, which was not previously reported.…”
Section: Discussionsupporting
confidence: 75%
“…Several groups of investigators have reported increased cardiovascular risk in patients with an abnormal vasomotor response to acetylcholine, an agonist for endothelial production of nitric oxide, in the coronary [20][21][22] or forearm circulations [23,24]. Impaired brachial artery flow-mediated dilation, as measured by ultrasound, is also associated with increased risk for cardiovascular events [25][26][27].…”
Section: Clinical Studies Of Endothelial Function and Their Clinical mentioning
confidence: 99%
“…[173][174][175] Indeed, in patients with essential hypertension, carotid wall thickening and left ventricular mass correlate with reduced endothelium-dependent vasodilation. 176,177 The ET system is activated in several but not all animal models of arterial hypertension. 171,[178][179][180][181][182][183][184][185][186][187] Correspondingly, ET plasma levels have been reported to be elevated in certain patients with essential hypertension, 188 but this is a subject to controversy.…”
Section: Endothelin and Endothelin Antagonists In Hypertensionmentioning
confidence: 99%